(untitled) (MAUSAM, 1991)
A new theory, using kinetic theory of gases, for dissolution of gaseous air pollutants and applicable both for wash out and rain out processes has been proposed. It has been shown that the current theory of wash out of gases given by Hales (1972) is a special case of the general theory proposed here.